Assessment of attitudes towards bioenergy by forestry experts in the Republic of Karelia - Trishkin, Maxim; Lopatin, Eugene; Gavrilova, Olga
The Republic of Karelia is situated in the northwestern part of Russia and represents approximately 1 % of the country’s territory. Forests cover 53 % of the total area, with 70 % of the total forest area available for harvesting. The bioenergy sector is relatively significant as it contributes 10 % to the total energy supply in Karelia, which as a fossil fuel deficient region is highly dependent on imported energy resources from other regions of the country. Therefore, the purpose of the study was to assess the role and position of bioenergy in the Republic of Karelia. It was done by exploring the perception of forestry professionals and forestry students towards bioenergy production in comparison with other forest uses. The role and position of bioenergy was identified through the assessment of the importance of landscape elements, ranking of adverse environmental effects on surrounding landscapes, input to the local economy and importance in planning principles. The results indicate that bioenergy production is perceived to have a low negative effect on the surrounding environment but also a low economic input to the local economy of the region. In addition, bioenergy is perceived to have a low influence on planning principles according to the opinions of the respondents. Statistically significant differences were found between the opinions of respondents with different occupations in regards to the main factors that negatively affect the surrounding environment. In general, the respondents indicated that bioenergy production is of moderate importance, although more research is needed in this field. 2017